The Influence of Volume II Tax Amnesty Policy and Modernization of Tax Information Systems on Individual Taxpayer Compliance with Tax Socialization as a Moderating Variable - Nurul Fatimah; Binsar H. Simanjuntak; Cipsas Cipsas (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study aims to determine the effect of tax amnesty volume II and modernization of tax information systems on individual taxpayer compliance with taxation socialization as a moderating variable. The variables used in this study are tax amnesty volume II, E Billing, E Filling, E SPT as the independent variable, individual taxpayer compliance as the dependent variable, and taxation socialization as a moderating variable.The data used is primary data with a questionnaire method obtained directly from individual taxpayers in the South Jakarta area. The sample selection was carried out using the Slovin formula approach and the simple random sampling method. The sample used is 78 individual taxpayers as respondents. The f-test aims at the effect of the independent variables on the dependent variable simultaneously. The results of the t-test showed that partially the variable of tax amnesty volume II and E Filling had a positive and significant effect on individual taxpayer compliance, while the E Billing and E SPT variables had a positive but not significant effect on individual taxpayer compliance. The results of the f test indicate that the variable tax amnesty volume II, E Billing, E Filling, E SPT has a positive and significant effect on individual taxpayer compliance. The results of testing the MRA regression hypothesis (Moderated Regression Analysis) of the tax socialization variable strengthen the effect of tax amnesty volume II and E SPT on individual taxpayer compliance. While the E Billing and E SPT variables had a positive but not significant effect on individual taxpayer compliance.